Evolutionary Programming (EP) based optimization technique for voltage stability improvement using reactive power dispatch / Mohd Idris Abdul Rahman - Abdul Rahman, Mohd Idris (2004)
This report presents an optimal reactive power dispatch based on Evolutionary Programming (EP) optimization technique for voltage stability improvement in power system. The objective of this study is to investigate the potential of reactive power dispatch (RPD) for improving the voltage stability condition along with improving the voltage profile in the system using the EP optimization technique. An EP optimization program is developed using MATLAB programming language. The objective function is to increase the voltage stability condition utilizing of a line-based index as the fitness function. A small test system is used for the implementation of this technique. The proposed optimization technique was validated on the IEEE Reliability Test System (IEEE-RTS) and result are included to realize the effectiveness of the proposed EP optimization technique.